2021
DOI: 10.1111/1365-2745.13729
|View full text |Cite|
|
Sign up to set email alerts
|

Tree growth increases through opposing above‐ground and below‐ground resource strategies

Abstract: 1. Studying functional traits and their relationships with tree growth has proved a powerful approach for understanding forest structure. These relationships are often expected to follow the classical resource economics perspective, where acquisitive leaves combined with acquisitive roots are expected to enhance resource uptake and tree growth. However, evidence for coordinated leaf and roots trait effects on growth is scarce and it remains poorly understood how these traits together determine tree growth. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Plant functional traits are physiological and morphological characteristics of plants that respond to environmental changes, significantly affecting the function of forest ecosystems ( Cappelli et al, 2020 ; Li X. et al, 2021 ; Weemstra et al, 2021 ). Specific leaf area (SLA) and leaf dry matter content (LDMC) are significantly correlated with particular plant resource utilization strategies and are extremely sensitive to climate change ( Kattge et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant functional traits are physiological and morphological characteristics of plants that respond to environmental changes, significantly affecting the function of forest ecosystems ( Cappelli et al, 2020 ; Li X. et al, 2021 ; Weemstra et al, 2021 ). Specific leaf area (SLA) and leaf dry matter content (LDMC) are significantly correlated with particular plant resource utilization strategies and are extremely sensitive to climate change ( Kattge et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The plant below-ground compartment economy is more controversial than that of the above-ground compartment because root traits do not consistently validate a root economic spectrum mirroring the leaf economic spectrum (Mommer & Weemstra, 2012;Weemstra et al, 2016Weemstra et al, , 2021. The coordination of many morphological and architectural traits with the root economic spectrum remains unclear, especially for woody species (Erktan et al, 2018;Kramer-Walter et al, 2016).…”
Section: Above-ground and Below-ground Individual Plant Strategies To...mentioning
confidence: 99%
“…The hypothesis assumes that root traits are analogous to leaf traits and therefore coordinate along the one-dimensional root economics spectrum (RES), which represents the trade-off between the acquisition and conservation traits [ 8 , 9 ]. However, some studies have suggested that the relationship between root traits is confounding, which does not concur with the hypothesis of RES [ 10 , 11 ]. Associated with the complexity of the root distribution environment and the diversity of exerting functions, the variation of root traits may be multidimensional [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%